Changes in hemoglobin values in elite cross-country skiers from 1987-1999 - Videman, T.; Lereim, I.; Hemmingsson, P.; Turner, M. S.; Rousseaux-Blanchi, M. P.; Jenoure, P.; Raas, E.; Schonhuber, H.; Rusko, H.; Stray-Gundersen, J. (Scandinavian Journal of Medicine & Science in Sports, 2000)
Hemoglobin data have been available from ski teams beginning from 1987, and from 1989 to 1999 we have followed hemoglobin values in elite cross-country skiers in international competitions. The mean values at the 1989 World Nordic Ski Championships were lower than population reference values, as would be expected from plasma volume expansion associated with endurance training. However, an increase, particularly in the maximal values, became obvious in 1994 and rose further in 1996. These extreme values provide both a health risk to the individual athlete and unfair competition. After a rule limiting hemoglobin values was introduced, the drop of the highest values was remarkable: among men 15 g/l (0.23 mmol/l) and among women 42 g/l (0.65 mmol/l). It would appear that the rule had achieved its goal of limiting extreme hemoglobin values. Yet the mean hemoglobin concentrations in men and women have continued to rise, suggesting the continued use of artificial methods to increase total hemoglobin mass. Scand J Med Sci Sports 2000 Apr;10(2):98-102